On the Oosterhoff dichotomy in the Galactic bulge: II. Kinematical distribution - Prudil, Zdeněk; Dékány, István; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present a kinematical study of RR Lyrae stars associated with two Oosterhoff groups in the Galactic bulge. We used data published in the first pap
Gesehen am 02.07.2019